Thyroid diseases are associated with coronavirus disease 2019 infection - Tian, Yutian; Zhao, Junyu; Wang, Tingting; Wang, Haipeng; Yao, Jinming; Wang, Song; Mou, Yaru (Frontiers in Endocrinology, 2022)
Backgrounds: In 2019, there was a global outbreak of new coronary pneumonia. Studies have found that the severity of patients with new coronary pneumonia may be related to their comorbidities. This article discusses the impact of thyroid disease on the severity of new coronary pneumonia through a meta-analysis, and provides new treatment ideas for the later treatment and recovery of new coronary pneumonia. Methods: Database including Pubmed, Embase, Cochrane library, Sinomed, CNKI and Wanfang for COVID-19 infection and thyroid diseases were searched. Reference lists of all eligible articles and related previous review articles were handing searched. Fifty-three articles were involved to conduct the meta-analysis. Results: Fifty-three articles with 12022 COVID-19 infection patients were included in this meta-analysis. The proportion of patients with thyroid diseases in all COVID-19 infection patients fluctuates between 0 and 88.46%. Of the 53 included studies, 22 studies reported the severity of COVID-19 infection and grouped. Fixed-effect model was used to merge OR values and the pooled effect size in favor of non-severe patients is 2.62 (95% CI=1.96-3.49, P<0.0001), means patients with severe COVID-19 infection are more likely to have thyroid diseases. The analysis sub-grouped by Asian and Europe shows that patients with COVID-19 severe infection in Asian are 3.77 times more likely to have thyroid diseases than non-severe patients (fixed-effect model: OR=3.77, 95%CI=2.66-5.35, P<0.00001). No significant statistical heterogeneity was found by the heterogeneity analysis (Chi2=19.85, P=0.34, I2=9%). Severe COVID-19 infection patients are more likely to complicated with hypothyroidism and low T3 syndrome. The pooled OR with fixed-effect model are 3.72 (95%CI=1.62-8.58, P=0.002) and 5.86 (95%CI=2.79-12.33, P<0.00001) respectively . Conclusion: COVID-19 infection patients with thyroid diseases are very common, and severe patients are more likely to have thyroid diseases. Asian COVID-19 infection, hypothyroidism patients and patients with low T3 syndrome are more likely to progress to severe condition.